Catalyst- and Solvent-Free Hydrophosphorylation of Ketones with Secondary Phosphine Oxides: Green Synthesis of Tertiary α-Hydroxyphosphine Oxides - Gusarova, Nina K.; Ivanova, Nina I.; Khrapova, Kseniya O.; Volkov, Pavel A.; Telezhkin, Anton A.; Larina, Lyudmila I.; Afonin, Andrei V.; Pavlov, Dmitry V.; Trofimov, Boris A. (Synthesis, 2020)
Tertiary α-hydroxyphosphine oxides have been synthesized via the catalyst- and solvent-free reaction between available secondary phosphine oxides and aliphatic, aromatic and heteroaromatic ketones at 20–62 °C in near to 96–98% yield. The developed method meets the requirements of green chemistry and the PASE (pot, atom, step economy) paradigm. According to quantum-chemical calculations at the B3LYP/6-311++G(d,p) level, the synthesized hydroxyphosphine oxides feature a weak (≈3 kcal·mol–1) O−H···O=P intramolecular hydrogen bond.
Keywords: ketones; secondary phosphine oxides; catalyst- and solvent-free addition; α-hydroxyphosphine oxides